1999
DOI: 10.1088/0022-3727/32/24/201
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence in organics

Abstract: There is growing interest in organic electroluminescence (EL). A great deal of progress has been made recently in improving the performance of various classes of organic EL devices. Some of these are now adequate for many applications. However, specialists focusing on selected aspects of organic EL devices have often lost contact with the general subject of EL. Therefore, a review covering all aspects of EL mechanisms and their experimental manifestation seemed necessary. This article is concerned with the new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(178 citation statements)
references
References 276 publications
7
161
0
1
Order By: Relevance
“…Complete genome sequence information of two strains of C. glutamicum ATCC 13032 is available, NC_003450 (Ikeda & Nakagawa, 2003) and BX927154 (Kalinowski et al, 2003), and the region of the dcw cluster is shown in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…Complete genome sequence information of two strains of C. glutamicum ATCC 13032 is available, NC_003450 (Ikeda & Nakagawa, 2003) and BX927154 (Kalinowski et al, 2003), and the region of the dcw cluster is shown in Fig. 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…5 Our geometry for the standard OLED consists of ITO as hole injector, N,NЈ-diphenyl-N,NЈ-(3-methilphenyl)-1, 1Ј-biphenil-4,4Јdiamine ͑TPD͒ as hole transporting layer ͑70 nm͒, 8-hydroxyquinoline aluminum (Alq 3 ) as emitting layer ͑70 nm͒, LiF ͑2 nm͒ tunnel barrier, and Al cathode. 1 The manganite work function LSMO is about 4.7-4.9 eV and is similar to that of ITO ( ITO ϳ5 eV) allowing the ITOmanganite substitution ͑Fig. 1͒.…”
Section: Methodsmentioning
confidence: 95%
“…A great effort has been made to enhance the device luminescence working on metal-organic interfaces, morphology, and charge transport in organic material. 1 Radiative recombination in OLEDs based on undoped -conjugated molecules arises from singlet excitons annihilation ͑triplet excitons normally do not contribute to photon emission͒. 2 The manipulation of the spin of carriers allows one to tune the electroluminescence ͑EL͒ efficiency by changing the relative population of singlet/triplet excitons.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies analyze the determination of the gaugino mass parameter M 1 via production and subsequent leptonic decay of neutralinos or selectrons in e + e − annihilation [10] - [15], via selectron production in e − e − scattering [15,16] or via associated selectron neutralino (LSP) production in eγ scattering processes [17,18]. In all these processes the M 1 dependence of the cross sections of the decay leptons, their polarization and forward-backward asymmetries result from a complex interplay of the M 1 dependence of the respective production and decay mechanism.…”
Section: -Dependencementioning
confidence: 99%